2007
DOI: 10.1007/s00431-006-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

Medication use during pregnancy and the risk of childhood cancer in the offspring

Abstract: The young age at onset of many cancers in childhood has led to investigations on maternal exposures during pregnancy. Data from a population-based case-control study in Germany (1992-1997) that included 1,867 cases and 2,057 controls was used to investigate this question. Maternal use of vitamin, folate or iron supplementation was associated with a reduced risk of non-Hodgkin lymphoma and tumors and, less clearly, with leukemia, but not with CNS tumors. An increased risk of neuroblastoma was associated most ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 47 publications
2
100
0
Order By: Relevance
“…Rates of nephroblastoma were significantly lower after mandatory US folic acid fortification, with stronger effects detected in infants (Linabery et al, 2012). Schuz et al (2007) observed similar results with the use of vitamins, folate, and/or iron supplements during pregnancy in Germany. In Brazil, fortification of foods has been mandatory since 2004 (www.anvisa.gov.br/alimentos/farinha.htm).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Rates of nephroblastoma were significantly lower after mandatory US folic acid fortification, with stronger effects detected in infants (Linabery et al, 2012). Schuz et al (2007) observed similar results with the use of vitamins, folate, and/or iron supplements during pregnancy in Germany. In Brazil, fortification of foods has been mandatory since 2004 (www.anvisa.gov.br/alimentos/farinha.htm).…”
Section: Discussionsupporting
confidence: 58%
“…Prenatal folic acid supplementation has been shown to decrease several congenital anomalies and is recommended for women of childbearing potential and during early pregnancy to decrease the risk of neural tube defects (NTD) in several countries (Berry et al, 1999). Multivitamin supplementation is thought to be associated with a reduced incidence of neuroblastoma, brain tumors, retinoblastoma, and nephroblastoma (Wilms' tumor) (Preston-Martin et al, 1998;Goh et al, 2007;Schuz et al, 2007). Folic acid food fortification was associated with a decline in neuroblastoma in Canada and nephroblastoma incidence in the United States (French et al, 2003;Grupp et al, 2011;Linabery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have not confirmed this purported protective effect (48,49) and has even reported an increased risk (46). Furthermore, most of these epidemiologic studies could not delineate the effect on cancer risk specific to folic acid from other vitamins in the supplements (50).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have reported a protective effect of periconceptional maternal folic acid supplementation on several pediatric cancers in the offspring including neuroblastoma and other brain tumors, acute lymphocytic leukemia, and non-Hodgkin's lymphoma (44)(45)(46)(47). However, some studies have not confirmed this purported protective effect (48,49) and has even reported an increased risk (46).…”
Section: Discussionmentioning
confidence: 99%
“…13]. Recently, however, a German casecontrol study found no association with maternal use of vitamins, folate, or iron supplements during pregnancy (14); a Swedish cohort study reported no association with vitamin use, but a weak inverse association with folic acid before pregnancy (15); and a Spanish study reported weak evidence of an inverse association of CBT with use of multivitamins or folic acid in the first month of pregnancy only (16). The variation among these results and their basis in use of different types of supplements in different time periods make them inconclusive.…”
Section: Introductionmentioning
confidence: 99%